Interferon-inducible protein 16 may be a biomarker and prognostic factor in renal cell carcinoma by bioinformatics analysis. Issue 1 (8th January 2021) - Yu, Baozhong; Zhang, Jiandong; Sun, Zejia; Cao, Peng; Zheng, Xiang; Gao, Zihao; Cao, Haoyuan; Zhang, Feilong; Wang, Wei
Abstract: Background: Renal cell carcinoma (RCC) accounts for 2% to 3% of all human malignancies and is the 9th most common malignancy in Western countries. Due to the development of surgical procedures and the use of novel drugs, survival has been significantly prolonged. However, current challenges include how to diagnose RCC earlier and how to overcome drug resistance. Methods: We explored the relationship between the transcription level of IFI16 and clinical data in RCC through various online databases, including ONCOMINE, GEPIA, HPA, Timer and COEXPEDIA. Results: In comparison with corresponding normal tissues, IFI16 mRNA expression levels were higher in kidney renal clear cell carcinoma (KIRC) and kidney renal papillary cell carcinoma (KIRP) tissues. In KIRC, the higher expression of IFI16 was associated with lower overall survival ( P = .037). In KIRP, the higher expression IFI16 was associated with lower disease-free survival and overall survival ( P = .037 and P = .011). In contrast, the IFI16 expression was negatively correlated with tumor purity in kidney chromophobe, KIRC and KIRP (all P < .05). In KIRC and KIRP, the expression of IFI16 was positively correlated with tumor-infiltrating immune cells (TIICs) (all P < .05), except macrophages in KIRP. In KIRC, the main TIICs were B cells, CD4 + T cells, neutrophils, and dendritic cells, while the main TIICs in the high amplification state were macrophage (all P < .0001). Functional enrichment analysis by gene ontology and Kyoto Encyclopedia of Genes and Genomes highlighted enrichment of neutrophil degranulation, phagocytosis and vesicle-mediated transport regulation, and pathways including tuberculosis, toxoplasmosis, phagosome, leishmaniasis, and Fc gamma R-mediated. Conclusions: IFI16 is overexpressed in RCC and may be an important oncogene in the progression of kidney. In addition, IFI16 may a marker for RCC diagnosis and prognosis, which may be related to immune infiltration.